KESIAPAN UPTD SMP NEGERI LATANG SEBAGAI SEKOLAH SIAGA BENCANA TERHADAP ABRASI PANTAI DI KECAMATAN PULAU PURA KABUPATEN ALOR - Djasibani, Benyamin Daniel; Samin, Mikael; Rahmawati, Arfita (Jurnal Geografi, 2023)
Research objectives (1) Knowing the geographical factors that cause abrasion can destroy the environment of the Latang State Middle School UPTD (2) Knowing how much the abrasion disaster risk index value has threatened the Latang State Middle School UPTD (3) Knowing the readiness of the Latang State Middle School UPTD as a disaster preparedness school against beach abrasion (4) Know the school's solution to tackling beach abrasion. This type of research is quantitative research in order to describe the problems under study to determine the Readiness of UPTD SMP Negeri Latang as a Coastal Abrasion Disaster Preparedness School in Pulau District, Alor Regency. Data collection techniques used (1) primary data (2) secondary data with the documentation method (3) observation, interview and questionnaire methods. The data analysis technique, namely geographic analysis, was used to determine the readiness of the Latang State Junior High School UPTD as a beach abrasion disaster preparedness school. The results of the study: (1) Based on the data obtained, it shows that the geographical factors that cause beach abrasion to UPTD SMP Negeri Latang are natural factors (2) Calculation of the risk index value for coastal abrasion disaster is 4 so that the conclusion is included in the high category (3) UPTD SMP Negeri Latang is ready to face when it experiences a beach abrasion disaster (4) The efforts made by UPTD SMP Negeri Latang are together with the school community to work together to minimize the risk of a beach abrasion disaster.